The Effect of Principal’s Academic Supervision and Work Motivation on Teacher’s Job Satisfaction - Aliska, Alen; Ahyani, Nur; Fitria, Happy (Journal of Social Work and Science Education, 2023)
The purpose of this study is to ascertain whether the academic oversight and work motivation of the principal at SMK Negeri 1 Prabumulih have an impact on teacher job satisfaction. In this study, 80 teachers were selected using the Slovin algorithm from a population of 100 teachers at Prabumulih State Vocational School 1, while the sampling is done by random sampling, This sort of study involves quantitative research with correlation and quantitative descriptive research methodologies. The research instrument is a questionnaire that has been evaluated for validity and reliability. The findings of the regression test, specifically simple linear regression and multiple linear regression using SPSS, support the research hypothesis that there is a substantial relationship between academic supervision and teacher job satisfaction